From Individual Drivers to Systemic Culture: Rethinking Employee Performance Improvement in Local Public Infrastructure Organizations - Dhike Noordestiasari Hanurajasa; Khusni; Hasanudin; Karim Pamela (PT. Caesarindo Triloka Persada, 2026)
This study revisits employee performance improvement in public sector organizations by shifting the focus from individual-based drivers to a systemic, culture-oriented perspective. Prior public human resource management research has primarily emphasized work motivation and organizational commitment as key predictors of performance. However, empirical evidence has been inconsistent, particularly within rule-based bureaucratic contexts. To address this gap, the study investigates whether organizational culture functions as a more fundamental mechanism shaping performance in local public infrastructure organizations. A quantitative explanatory design was employed, utilizing cross-sectional survey data collected from both civil servants and non-civil servants working in public infrastructure organizations in Majalengka Regency, Indonesia. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that organizational culture exerts a strong and statistically significant influence on employee performance, whereas work motivation and organizational commitment have weak and non-significant effects. These results suggest that performance in public infrastructure organizations is primarily driven by systemic cultural mechanisms rather than individual psychological factors. This study contributes to the public management literature by reframing performance improvement strategies in the public sector, positioning organizational culture as a foundational driver of performance, and offering theoretical and policy-relevant insights for bureaucratic reform.